DEVELOPMENT OF ICT-BASED LEARNING MEDIA IN SUBTEMA PPKN LESSONS THANKFUL FOR DIVERSITY TO INCREASE STUDENTS' LEARNING OUTCOMES IN CLASS IV SD NEGERI 106161 LAUT DENDANG - Chairun Nisyah Rambe; Reh Bungana Br. Perangin-angin; Sri Adhi Sri Adhi (SENSEI RESEARCH CENTER, 2022)
This study aims to describe the level of feasibility and effectiveness of developing ICT-based learning media in the form of interactive power points on the sub-theme of being grateful for diversity. This research was conducted at the public elementary school 106161 Laut Dendang, Percut Sei Tuan District. The subjects of this study were all fourth grade students of public elementary school 106161 Laut Dendang. The research method is Borg & Gall development research. The results showed (1) Based on the results of the analysis of ICT-based learning media products on the sub-theme of being grateful for the diversity of the experts, it was stated that it was very effective and suitable for use with the criteria of the validity of material experts 85.42%, design experts 91.00%, and linguists 85 ,00 %; 2) ICT-based learning media is categorized as practical because ICT-based learning media results from student responses have increased; and 3) ICT-based learning media is said to be effectively used in learning with the assumption that students' understanding of the sub-theme of being grateful for diversity is higher when using ICT-based learning media on the sub-theme of being grateful for diversity.